Utilization of DNA double-strand breaks for biodosimetry of ionizing radiation exposure - Andrey Bushmanov; Natalia Vorobyeva; Daria Molodtsova; Andreyan N. Osipov (Environmental Advances, 2022)
Analysis of DNA double-strand breaks (DSBs) is an important novel tool to estimate the biological effects of ionizing radiation. Despite the large number of developed methods for assessing DNA damage, each method has its own advantages and disadvantages. In this paper we provide a review of the methods for assessing DSBs in DNA and the possibility of the practical use of such methods for biodosimetry of ionizing radiation exposure. Specifically, they include methods based on assessing the degree of DNA fragmentation (pulsed-field gel electrophoresis, DNA comet assay), enzymatic methods (terminal deoxynucleotidyl transferase dUTP nick end labeling) and methods based on the quantitative analysis of proteins involved in DNA DSBs repair (immunocytochemical analysis of foci of DNA repair proteins using fluorescence microscopy, analysis of DNA repair proteins using fluorescence flow cytometry, imaging flow cytometry). Utilization of DNA DSBs for biodosimetry of ionizing radiation exposure is a new niche for fast screening and is quite sensitive to reflect the biological importance of the radiation exposure.